Family Migration and Relative Earnings Potentials - Mette Foged (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
I document that couples are more likely to migrate if household income is disproportionally due to one partner, and that families react equally strong to a male and female relative earnings advantage. A unitarian model of family migration in which families may discount wives' private gains is used to derive testable implications regarding the type of couples that select into migrating. The empirical tests show that gender-neutral family migration cannot be rejected against the alternative of husband-centered migration. The lower response of family migration to the human capital held wives than the human capital of husbands, documented in the literature, may be attributed to more intense colocation problems and lower income among female-headed households. The more severe colocation problem stems from stronger educational homogamy among highly educated women relative to highly educated men. The results hold for internal as well as international migration of couples
Keywords: F22; D19; J61; 330; Internationalmigration; familymigration; colocationproblem; selection